Behaviour of Black-throated Diver Gavia arctica and Red-throated Diver Gavia stellata during autumn migration stopover - Polak, Marcin; Ciach, Michał (Ornis Svecica, 2021)
The stopover behaviour of Black-throated Divers Gavia arctica and Red-throated Divers Gavia stellata during autumn migration was observed in two sites in Poland. Differences in time-activity budget and diving pattern were recorded from mid-October to mid-January of 2004 and 2005. A total of 1,516 minutes of observation was achieved. Birds spent their time diving (60.7%), followed by preening (14.8%), surface swimming (12.5%), and other activities (12%). The feeding pattern of Red-throated Divers and Black-throated Divers was similar. Immature birds had significantly longer dives than adults and they made longer dive-pause intervals. This is suggested to be caused by the differences between age classes in detecting and capturing prey. Moreover, our results show that, in autumn, first-year divers spent less time foraging than adult birds, instead spending more time resting and surface swimming.